On the complexity of skew arithmetic - van der Hoeven, Joris (Applicable algebra in engineering, communication and computing, 2016)
In this paper, we study the complexity of several basic operations on linear differential operators with polynomial coefficients. As in the case of ordinary polynomials, we show that these complexities can be expressed almost linearly in terms of the cost of multiplication.